Empowering Students Through Religious Values: Enhancing Life Skills and Leadership in Educational Management - Kulsum, Umi; Apriyani, Nurwinda (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to explore the impact of religious culture on the development of students' life skills in schools. Using a qualitative case study research design, this study explores how the integration of religious values in the educational environment can influence the formation of students' character, social, emotional, leadership, and resilience skills. Data were collected through in-depth interviews with principals, teachers, extracurricular supervisors, and students, as well as direct observation of activities at school. The findings of the study indicate that the application of religious values has implications for the development of students' life skills, emphasizing moral, ethical, and emotional management aspects in everyday life. The integration of religious values in formal and extracurricular learning helps students build leadership skills based on collaboration and increases their resilience in facing academic and social challenges. Practically, the results of this study imply the need for schools to continue to strengthen the integration of religious values in every educational activity in order to prepare students to face increasingly complex life challenges. This study contributes to the development of character-based educational management theory, as well as providing insight for educational practitioners in designing learning environments that support students' holistic development.